Sistem Informasi Repository Laporan Praktek Kerja Lapangan (PKL) Mahasiswa Berbasis Android - Olha Musa; Fitriyanti Suleman (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
The repository is a set of services offered by SMK Negeri 1 Suwawa for managing and storing student field work practice reports. The aim of the research is to build a repository information system for student field work practice reports to improve academic services at the Android-based SMK Negeri 1 Suwawa. The research method used is the research and development method, where system development is based on the results of identification, analysis of previous systems and collection of primary and secondary data. System testing is carried out using Whitebox testing by selecting modules from the registration web which are converted into flowcharts, then calculating Cyclometic Complexity (CC) and Blackbox testing. The test results show that the Cyclomatic Complexity (CC) is 2, and the test results V (G) = 2. Based on these results, it can be concluded that the student PKL report repository information system is designed on two different platforms, namely the website and smartphone.